Analisis Model Contextual Teaching and Learning terhadap Hasil Belajar IPS Siswa - Latifah Meynawati; Mochammad Amirul Rifqi Haryadi; Rachmi Nursifa Yahya; Sekar Ayu Cahyani; Syva Lestiyani Dewi; Tuti Istianti (Journal on Education, 2022)
Since a teacher's ability to instruct in class has a direct bearing on students' hopes for their own education, it's crucial that they acquire effective teaching strategies through the use of proven pedagogical models. Teachers can implement the Contextual Teaching and Learning Model in the classroom to change the way their students learn. The primary purpose of this research is to evaluate the CTL learning model's potential for improving the quality of education in the primary grades by promoting student engagement and encouraging collaborative efforts to improve social studies instruction.